Enteric parasitosis in school children: importance of associated parasites (Revista Venezolana de Salud Pública, 2020)
Simultaneous presence of various enteric parasites can have important clinical, epidemiological and therapeutic implications. A retrospective study of correlational type was carried out to determine Fager’s Affinity Index in a group of polyparasitized schoolchildren from Bolivar state, Venezuela. Between 2007 and 2016, 1277 children between 5 and 15 years of age from 11 schools (10 in the Heres municipality and 1 in the Caroní municipality) were evaluated. Gender distribution was homogeneous in the schoolchildren evaluated (n = 613 female and n = 664 male). Of the 1277 samples analyzed, 811 (63.7%) showed enteric parasites in their evolutionary form. The most common were the chromists represented by Blastocystis spp. (49.3%), followed by the protozoa Endolimax nana (14.5%) and Entamoeba coli (11.7%), and lastly the helminths, where the most frequent was Ascaris lumbricoides (5.5%). Schoolchildren were polyparasitized in 43.2% of cases, the most commonly associated parasite being Blastocystis spp. with 90% of cases followed by E. nana (43.1%) and E. coli (35.4%). The affinity indices (IAB) and "t" tests carried out indicated an association between Blastocystis spp. and the protozoa G. intestinalis, E. nana and E. coli and between Trichuris trichiura and A. lumbricoides geohelminths.
Keywords: intestinal parasitosis; association; parasites; school children